Traumatic Loss of the Ulnar Condyle of the Proximal Phalanx of the Ring Finger Repaired with a Palmar Plate Flap: a Case Report - Piotuch, B.; Zyluk, A. (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2015)
We report on an acute, open PIP joint injury to the ring finger with associated loss of the ulnar condyle of the proximal phalanx, which was repaired by the removal of bone fragments and replacement of the bone defect with a proximally based palmar plate flap.
Keywords: PIP joint injury; bone defect; palmar plate flap